Transcriptomic Remodeling Occurs During Cambium Activation and Xylem Cell Development in Taxodium ascendens - Kebing Du; Youming Xu; Ningning Wang; Liyuan Qin; Jieyun Tao (Current Issues in Molecular Biology)
Taxodium ascendens has been extensively cultivated in the wetlands of the Yangtze River in south China and has significantly contributed to ecology and timber production. Until now, research on T. ascendens genomics has yet to be conducted due to its large and complex genome, which hinders the development of T. ascendens genomic resources. Combined with the microstructural changes during cambium cell differentiation across various growth periods, we investigate the transcriptome expression and regulatory mechanisms governing cambium activity in T. ascendens. Using RNA sequencing (RNA-Seq) technology, we identified the genes involved in the cambium development of cells at three stages (dormancy, reactivation, and activity). These genes encode the regulatory and control factors associated with the cambial activity, cell division, cell expansion, and biosynthesis of cell wall components. Blast comparison revealed that three genes (TR_DN69961_c0_g1, TRINITY_DN17100_c1_g1, TRINITY_DN111727_c0_g1) from the MYB and NAC families might regulate transcription during lignin formation in wood thickening. These results illustrate the dynamic changes in the transcriptional network during vascular cambium development. Additionally, they shed light on the genetic regulation mechanism of secondary growth in T. ascendens and guide further elucidation of the candidate genes involved in regulating cambium differentiation and wood formation.